2001
DOI: 10.1128/jvi.75.1.181-191.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Human Immunodeficiency Virus Type 1gagGene Encodes an Internal Ribosome Entry Site

Abstract: Several retroviruses have recently been shown to promote translation of their gag gene products by internal ribosome entry. In this report, we show that mRNAs containing the human immunodeficiency virus type 1 (HIV-1) gag open reading frame (ORF) exhibit internal ribosome entry site (IRES) activity that can promote translational initiation of Pr55 gag . Remarkably, this IRES activity is driven by sequences within the gag ORF itself and is not dependent on the native gag 5-untranslated region (UTR). This cap-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 97 publications
8
161
0
Order By: Relevance
“…Consistent with the ELISA data, less Gag was observed for the R-Gag proteins irrespective of the presence of the SL epitope. In addition to the 55-kDa Gag signal, a second band migrating at ϳ40 kDa was observed that presumably originates from an internal translation event as was described for another Gag expression system (35).…”
Section: Expression Of the Hiv-1 Pr55 Gag Polyprotein In The Murine Tmentioning
confidence: 94%
“…Consistent with the ELISA data, less Gag was observed for the R-Gag proteins irrespective of the presence of the SL epitope. In addition to the 55-kDa Gag signal, a second band migrating at ϳ40 kDa was observed that presumably originates from an internal translation event as was described for another Gag expression system (35).…”
Section: Expression Of the Hiv-1 Pr55 Gag Polyprotein In The Murine Tmentioning
confidence: 94%
“…YU-2 Env was cloned into the MluI and PspOM1 sites of a modified pCI expression construct (Promega), modified to contain hepatitis B virus PRE to enable high-level, rev-independent Env expression (8,42), to generate a gp160 expression construct that contained both T7 and cytomegalovirus promoters. T202G, K421D, I423S, P437A, P438A, and G441V amino acid changes (numbering according to HXB2) were introduced into the coreceptor-binding site of YU-2 Env with specific oligonucleotides and the Quikchange site-directed mutagenesis kit (Stratagene), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the finished SIINFEKL-appended ORFs was transferred into the pCI-PRE vector backbone (23) by transferring an NheI-StuI fragment of each vaccinia transfer vector into pCIgag prepared by digestion with XbaI, blunting with T4 DNA polymerase, then digestion with NheI. A vector encoding wild-type Gag appended with SIINFEKL epitope was constructed by ligating an NheI-SphI fragment of pIgag into pUbRgag prepared by digestion with NheI and SphI.…”
mentioning
confidence: 99%